Benign Neglect or Active Destruction? A Critical Analysis of Refugee and Informal Sector Policy and Practice in South Africa - Crush, Jonathan; Skinner, Caroline; Stulgaitis, Manal (African Human Mobility Review, 2021)
To fully comprehend the disabling policy environment in which refugees in South Africa attempt to carve out a livelihood, it is important to analyse two largely independent but overlapping streams of policy-making. This paper first examines the post-apartheid refugee protection regime and traces how and why a generous right-based approach has been progressively comprised by growing restrictionism, exclusion and bureaucratic ineptitude. The 2017 Refugees Amendment Act and White Paper on International Migration represent the culmination of this process. While both are probably unimplementable and will be the subject of numerous court challenges, they can be seen as a major retreat and an increasing failure to protect. The second part of the paper traces the history of national and municipal informal sector governance since the early 1990s. Since so many refugees are forced or choose to work informally, the uncertainty and confusion this history has produced is of particular relevance. Refugee entrepreneurs have regularly been the victims of general and targeted informal sector eradication campaigns.